Microglia Express Insulin-Like Growth Factor-1 in the Hippocampus of Aged APPswe/PS1ΔE9 Transgenic Mice - Myhre, Christa Løth; Thygesen, Camilla; Villadsen, Birgitte; Vollerup, Jeanette; Ilkjær, Laura; Krohn, Katrine Tækker; Grebing, Manuela; Zhao, Shuainan; Khan, Asif Manzoor; Dissing-Olesen, Lasse; Jensen, Morten Skovgaard; Babcock, Alicia A.; et al. (Frontiers in Cellular Neuroscience, 2019)
Insulin-like growth factor-1 (IGF-1) is a pleiotrophic molecule with neurotrophic and immunomodulatory functions. Knowing the capacity of chronically activated microglia to produce IGF-1 may therefore show essential to promote beneficial microglial functions in Alzheimer’s disease. Here, we investigated the expression of IGF-1 mRNA along with the expression of tumor necrosis factor (TNF) mRNA, and the amyloid-β (Aβ) plaque load in the hippocampus of 3- to 24-month-old APPswe/PS1dE9 transgenic (Tg) and wild-type (WT) mice. As IGF-1, in particular, is implicated in neurogenesis we also monitored the proliferation of cells in the subgranular zone (sgz) of the dentate gyrus. We found that the Aβ plaque load reached a plateau in aged APPswe/PS1dE9 Tg mice, and that microglial reactivity and hippocampal IGF-1 and TNF mRNA levels were significantly elevated in aged APPswe/PS1dE9 Tg mice. IGF-1 mRNA was expressed in subsets of sgz cells, likely neuroblasts, and neurons in both genotypes, regardless of age, as well as in glial-like cells which double in situ hybridization showed to be IGF1 mRNA+/CD11b mRNA+ cells, i.e. IGF-1 mRNA expressing microglia. Quantification showed a two-fold increase in the number of microglia and IGF-1 mRNA+ microglia in the molecular layer of the dentate gyrus in aged APPswe/PS1dE9 Tg mice. Exposure of primary murine microglia and BV2 cells to Aβ42 did not affect IGF-1 mRNA expression. IGF-1 mRNA levels remained constant in WT mice with aging, unlike TNF mRNA levels which increased with aging. Finally, sgz cell proliferation decreased with age, regardless of genotype and the increased IGF-1 and TNF mRNA levels. In conclusion, our results suggest that the increased IGF-1 mRNA levels can be ascribed to a larger number of IGF-1 mRNA-expressing microglia in the aged APPswe/PS1dE9 Tg mice. The finding that subsets of microglia retain the capacity to express IGF-1 mRNA in the aged APPswe/PS1dE9 Tg mice is encouraging, considering the beneficial therapeutic potential of modulating microglial production of IGF-1 in AD.